Rancang Bangun Pembimbingan Akademik Skripsi Berdasarkan Antrian Reservasi - Ira Kumalasari; Dyah Lestari; Febrianto Alqodri (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2024)
Student thesis guidance is the final stage in the process of completing a Bachelor's degree at the University level. During the thesis process, students are required to be guided by lecturers who have qualifications relevant to the title of their thesis. The large number of guidance provided to lecturers, and the limited space to receive students, requires an application to regulate the use of rooms and thesis guidance. Therefore, an application is needed that can accommodate the thesis guidance process and room use. The student thesis guidance application uses the First In First Out (FIFO) algorithm and is integrated with the Thesis and Final Project Information System (SISINTA) and the Administration Information System (SIADMIN). The waterfall development method used includes needs analysis, design, implementation, and testing. This application supports reservation, verification, monitoring, and scheduling features. The application can function 100% according to needs and can be used to increase the efficiency and transparency of the thesis guidance process.